Legal Imlications for Aying Ages Based on the Decree of the Governor Regarding Labor Intensive Minimum Wages that Have Been Canceled by the Sureme Court and/or Already Change Years - Irwan Saleh Indraraja (IHSA Institute, 2021)
The discussion in this legal study relates to the decision of the governor of West Java which stiulates the minimum wage for labor Intensive Industries (UMK) for certain tyes of garment industry in urwakarta regency, bogor regency, and bekasi city for 2017, effective in July 2017, whose value is lower than the regency/city minimum wage for the same year set on November 21, 2016, effective as of January 2017. The three gubernatorial decrees above were met with oosition from the labor unions in the Kab. urwakarta, Kab. Bogor, and Kota Bekasi, West Java, also from the central level trade unions. Federation of Indonesian metal workers union T. Dada Indonesia, metal workers union federation of Indonesian metal Workers Union T. The decision of the Administrative Court which declared invalid and ordered the Governor of West Java to revoke it: Decree of the Governor of West Java Number: 561/Ke.644-Yanbangsos/2017 concerning Minimum Wages for Certain Labor-Intensive Industries for Garment/Aarel Industries in the urwakarta Regency of 2017 dated July 24, 2017